French at the Post-Secondary Level: the CPF Perspective - Manzer, Kathryn (Canadian Journal of Higher Education, 1989)
Canadian Parents for French is a national organization dedicated to promoting and creating opportunities for young Canadians to learn French as a second language. This article describes the organization's developing concern at the paucity of opportunities for anglophone students who are fluent in French to pursue bilingual education at the post-secondary level, the organization's role in focusing attention on this issue, and organizational policy as it evolved through regional and national conferences, surveys and reports.